2013
DOI: 10.1097/fbp.0b013e3283618ac8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in morphine reward in a model of neuropathic pain

Abstract: In addition to sensory disturbances, neuropathic pain is associated with an ongoing and persistent negative affective state. This condition may be reflected as altered sensitivity to rewarding stimuli. We examined this hypothesis by testing whether the rewarding properties of morphine are altered in a rat model of neuropathic pain. Neuropathic pain was induced by chronic constriction of the common sciatic nerve. Drug reward was assessed using an unbiased, three-compartment conditioned place preference (CPP) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 22 publications
0
34
2
Order By: Relevance
“…Evidence from a number of groups also suggests that the mesolimbic dopamine system modulates the perception of nociceptive information, the efficacy of pain medications, and the affective symptoms of chronic pain (Baliki et al, 2010, Cahill et al, 2013, Terzi et al, 2014). Dennis and Melzack (1983) first demonstrated that dopaminergic agents improve symptoms of pain and promote analgesia.…”
Section: Chronic Pain Modulates the Mesolimbic Circuitrymentioning
confidence: 99%
“…Evidence from a number of groups also suggests that the mesolimbic dopamine system modulates the perception of nociceptive information, the efficacy of pain medications, and the affective symptoms of chronic pain (Baliki et al, 2010, Cahill et al, 2013, Terzi et al, 2014). Dennis and Melzack (1983) first demonstrated that dopaminergic agents improve symptoms of pain and promote analgesia.…”
Section: Chronic Pain Modulates the Mesolimbic Circuitrymentioning
confidence: 99%
“…In animal models, chronic pain alters the motivation to obtain reward (Cahill et al, 2013;Wade et al, 2013) and leads to preference of larger infrequent rewards (Pais-Vieira et al, 2009). In experimental acute pain in humans, motivation to obtain reward was shown to be increased without affecting the self-reported hedonic response to reward (Gandhi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As described above, the pathogenesis of neuropathic pain and the effect of the disease on higher brain function have been widely investigated [26][27][28] ; however, the effect of neuropathic pain on peripheral organs remains unclear. We previously demonstrated that increased expression of uridine diphosphate glucuronosyltransferase (UGT)2B in the liver was a major cause of morphine resistance in neuropathic pain.…”
mentioning
confidence: 99%